Answer :

Here,


Now, we have to find adj A and for that we have to find co-factors:












Calculating A (adj A)






= -132I


Calculating (adj A)A






= -132I


Calculating |A|.I


Expanding along C1, we get




= [4(0 – 42) – (1){45 – 21} + 2(30 – 0 )]I


= [4(-42) – 1(24) + 2(30)] I


= (-168 – 24 + 60)I


= -132I


Thus, A(adj A) = (adj A)A = |A|I = -132I


A(adj A) = (adj A)A = |A|I


Hence Proved


Ans.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers